KONSEP DASAR DAN ASAS-ASAS DALAM HUKUM PERIKATAN - Fadila, Nurul; Sa’diyah, Kholifatus; Krisdayanti, Krisdayanti (universitas Islam Zainul Hasan Genggong, 2024)
Abstract : This article explains the basic concepts and principles in contract law, where a bond is a legal relationship between two parties in the field of assets, where one party (the creditor) is entitled to a performance and the other party, the debtor, is obliged to fulfill that performance. Basically, an agreement is born/exists because there is a law or agreement that gives birth to the agreement. The legal basis for civil legal obligations is one of the important aspects of the legal system that regulates relationships between individuals or legal entities. This research uses qualitative research methods with a library approach. Library research is used to collect data from literature such as books, notes and reports of previous research results.